Trichinellosis in developing countries: is it neglected? - Bruschi, Fabrizio (The Journal of Infection in Developing Countries, 2012)
Trichinellosis is a foodborne zoonosis caused by the parasitic nematode Trichinella, which is characterized by an extremely wide host range and geographical distribution. The aim of the present review is to provide epidemiological information on animal and human trichinellosis occurring in developing countries in the different continents, where cooking habits along with poverty and poor sanitary conditions and lack of veterinary controls may facilitate the occurrence of human trichinellosis outbreaks. Countries have been considered according to the six regions designated by the World Health Organization (WHO): 1) WHO African Region, 2) WHO Region of the Americas, 3) WHO South-East Asia Region, 4) WHO European Region, 5) WHO Eastern Mediterranean Region, and 6) WHO Western Pacific Region. For the purposes of this article, developing countries are defined as those not industrialised according to the World Economic Outlook Report of the International Monetary Fund (http://www.imf.org); however, with regard to the European Region of WHO, only those countries that are not member states of the European Union will be considered.